Hyperkalemia burden and treatment patterns in Chinese patients on hemodialysis: final analysis of a prospective multicenter cohort study (PRECEDE-K) - Haijiao Jin; Renhua Lu; Lihong Zhang; Li Yao; Guojian Shao; Li Zuo; Shuguang Qin; Xinzhou Zhang; Qinghong Zhang; Weimin Yu; Qun Luo; Yuqing Ren; et al. (Renal Failure)
Objectives Patients with end-stage renal disease (ESRD) on hemodialysis (HD) are at risk for hyperkalemia (HK), associated with cardiac arrhythmia and sudden death. Data on the burden of HK and management techniques among HD patients in China are still scarce. This study assessed the treatment modalities, recurrence, and prevalence of HK in Chinese HD patients.Methods In this prospective cohort study conducted from May 2021 to July 2022, patients aged ≥18 years who had ESRD and were on HD were enrolled from 15 centers in China (up to 6 months).Results Overall, 600 patients were enrolled. At the baseline visit, mean (± standard deviation) urea reduction ratio was 68.0% ± 9.70 and Kt/V was 1.45 ± 0.496. Over 6 months, 453 (75.5%) patients experienced HK, of whom 356 (78.6%) recurred. Within 1, 2, 3, 4, 5, and 6 months, 203 (44.8%), 262 (57.8%), 300 (66.2%), 326 (72.0%), 347 (76.6%), and 356 (78.6%) patients had at least one HK recurrence event, respectively. The proportions of patients with ≥1, 2, 3, 4, 5, or 6 HK recurrence events were 356 (78.6%), 306 (67.5%), 250 (55.2%), 208 (45.9%), 161 (35.5%), and 110 (24.3%), respectively. Among the 453 patients who experienced HK, only 24 (5.3%) were treated with potassium binders: seven (1.5%) with sodium polystyrene sulfonate, 13 (2.9%) with calcium polystyrene sulfonate, and six (1.3%) with sodium zirconium cyclosilicate.Conclusion Since HK is a chronic illness, long-term care is necessary. Patients on HD should have effective potassium management on non-dialysis days, yet our real-world population rarely used potassium binders.Trial registration ClinicalTrials.gov Identifier NCT04799067